Determination of Sex by Discriminant Function Analysis of Lateral Radiographic Cephalometry - Raj Kumar Badam; M Manjunath; M S Rani (Wolters Kluwer Medknow Publications, 2011)
Objective: The present study is an attempt to develop a method to determine sex from the skull with lateral cephalometric radiograph using discriminant function analysis. Study design : The superciliary ridges, frontal sinuses, sella, cranial base and mastoid process were adopted as objects of lateral radiographic cephalometnc measurements. The present study included cephalometric radiographs of 100 Indian adults chosen randomly from the records, each cephalometric radiograph was traced and nine linear and five angular measurements and one proportion were recorded for each case. Results: Using the discriminant functional analysis, the randomly chosen 100 adult patent cephalometric radiographs were classified into two sexual groups 84% of accuracy. Conclusion: From the results of the present study, it may be concluded that sex determination can be done with greater reliability.